Pengaruh Persepsi Kemudahan Penggunaan, Kepercayaan, dan Pengalaman Konsumen terhadap Niat Beli Ulang Pada Aplikasi Shopee - Wijaya, Shanda; Rohman, Fatchur (SAFE-Network, 2025)
The objective of this quantitative explanatory research is to assess and analyze the direct influence of perceived ease of use, trust, and consumer experience on the repurchase intention of Shopee application users in Malang City. Using a purposive sampling technique, 100 people with the minimum age of seventeen years who live in Malang City and have purchased goods via Shopee application at least twice were selected as the respondents. The instruments have been tested for validity and reliability, and the data have passed the classical assumption test and analyzed through multiple linear regression. The results of hypothesis testing demonstrate that perceived ease of use, trust, and consumer experience positively and significantly influence the repurchase intention of Shopee application users.